Pasantías En El Ministerio De Hacienda Y Crédito Público (2023)
This degree work exposes the competencies acquired in the sub directorate of Human Talent Management of the Ministry of Finance and Public Credit. During the development of different activities, analysis of the financial and fiscal behavior of the health system, evaluation of policies of the social security system and legislative proposals, as well as the management of financial models of the health regimes were carried out.